To solve the equation \( 3w^2 - 10w = 8 \) by factoring, we'll first bring all terms to one side to set the equation to zero:
\[ 3w^2 - 10w - 8 = 0 \]
Next, we'll factor the quadratic equation. We need to find two numbers that multiply to \( 3 \times -8 = -24 \) and add to \(-10\).
The two numbers that meet these criteria are \(-12\) and \(2\) because:
\(-12 + 2 = -10\) and \(-12 \times 2 = -24\).
Now, we can rewrite the quadratic as:
\[ 3w^2 - 12w + 2w - 8 = 0 \]
Now, group the terms:
\[ (3w^2 - 12w) + (2w - 8) = 0 \]
Factor by grouping:
\[ 3w(w - 4) + 2(w - 4) = 0 \]
Now factor out the common factor \((w - 4)\):
\[ (w - 4)(3w + 2) = 0 \]
Now we can set each factor to zero:
-
\( w - 4 = 0 \)
- \( w = 4 \)
-
\( 3w + 2 = 0 \)
- \( 3w = -2 \)
- \( w = -\frac{2}{3} \)
Thus, the solutions are:
\[ w = 4 \quad \text{and} \quad w = -\frac{2}{3} \]
So the final answer is:
A. \( w = 4, -\frac{2}{3} \) (Enter your response as: 4, -2/3)